0
$\begingroup$

We use the definitions $$F(k)=\mathcal{F}(f(x))=\frac{1}{\sqrt{2\pi}}\int_{-\infty}^{\infty} e^{-ikx}f(x) \ dx,$$ where the inverse is defined as $$f(x)=\mathcal{F}^{-1}(F(k))=\frac{1}{\sqrt{2\pi}}\int_{-\infty}^{\infty} e^{ikx}F(k) \ dk.$$

Consider the Fourier transform pair commonly found in tables:

enter image description here

Given the definition of the Fourier transform and its inverse as already defined, are these transformations symmetric? e.g. is $$\mathcal{F}\left(\frac{\sin(ax)}{x}\right)=\sqrt{\frac{\pi}{2}}H(a-k)H(a+k)$$ the same as $$\mathcal{F}^{-1}\left(\frac{\sin(ak)}{k}\right)=\sqrt{\frac{\pi}{2}}H(a-x)H(a+x)?$$

Edit:

\begin{align} \mathcal{F}^{-1}_k(F(k)\cos(ckt))&=\frac{1}{\sqrt{2\pi}}\int_{-\infty}^{\infty} F(k) \cos(ckt) e^{ikx} \ dk \\ &=\frac{1}{2\sqrt{2\pi}}\int_{-\infty}^{\infty} F(k) (e^{ckti}+e^{-ckti}) e^{ikx} \ dk \\ &=\frac{1}{2\sqrt{2\pi}}\int_{-\infty}^{\infty} F(k) e^{ik(x+ct)} \ dk+\frac{1}{2\sqrt{2\pi}}\int_{-\infty}^{\infty} F(k) e^{ik(x-ct)} \ dk \\ &=\frac{1}{2}\left(f(x+ct)+f(x-ct)\right). \end{align} (recalling that $f(x)=\mathcal{F}^{-1}(F(k))$)

$\endgroup$
2
$\begingroup$

Almost: with your normalization, we have that $$\mathscr{F}\{f\}(x)=\mathscr{F}^{-1}\{f\}(-x)$$ i.e. $$\mathscr{F}^2\{f\}(x)=f(-x)$$ So if $$\mathscr{F}\left\{\frac{\sin(ax)}{x}\right\}(k)=\sqrt{\frac{\pi}{2}}H(a-k)H(a+k)$$ Then $$\mathscr{F}^{-1}\left\{\frac{\sin(ak)}{k}\right\}(x)=\sqrt{\frac{\pi}{2}}H(a+x)H(a-x)$$

| cite | improve this answer | |
$\endgroup$
  • $\begingroup$ Are you please able to correct my example? I'm still a bit confused. $\endgroup$ – Steven Apr 29 '19 at 12:55
  • $\begingroup$ @Stuart-JamesBurney Your result was good, because the result of the FT is even. $\endgroup$ – Botond Apr 29 '19 at 13:00
  • $\begingroup$ Yep, I see that now. I have something that's niggling me though. Consider $$\mathcal{F}\left(f(x)cos(ax)\right)=\frac{1}{2}\left(F(k-a)+F(k+a)\right).$$ By using the definition of the inverse Fourier transform, I have shown that $$\mathcal{F}^{-1}\left(F(k)cos(ckt)\right)=\frac{1}{2}\left(f(x+ct)+f(x-ct))\right.$$ Is this because this too is even? $\endgroup$ – Steven Apr 29 '19 at 13:05
  • $\begingroup$ @Stuart-JamesBurney is $F(k)=\mathscr{F}\{f(x)\}(k)$? $\endgroup$ – Botond Apr 29 '19 at 13:13
  • 1
    $\begingroup$ @Stuart-JamesBurney I checked everything multiple times. If $\mathscr{F}\{f\}(k)=\int \mathrm{d}x \, e^{-ikx}f(x)$, then $\mathscr{F}\{f\}(-k)=\int \mathrm{d}x \, e^{ikx}f(x)=\mathscr{F}^{-1}\{f\}(k)$. I checked $\mathscr{F}\{f(x)\cos(ax)\}(k)$ on wikipedia, and it's correct as well. And $\mathscr{F}\{f(x-a)\}(k)=F(k)e^{-ika}$ (from wikipedia), so your inverses are correct as well. $\endgroup$ – Botond Apr 29 '19 at 14:27

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.